Design and construction of a small open-air wind tunnel without contraction and diffuser - Marzuki, Omar Faruqi; Alik, Muhammad Aliff Najmi; Yi, Ellie Lih Teo; Mohd Rafie, Azmin Shakrine; Pendek, Zainol Ariffin; Adam, Nor Mariah (Aeronautical and Astronautical Society, 2024)
This paper presents the design and construction of a small open jet wind tunnel without the contraction and diffuser. The wind tunnel is intended for experimental testing of models in a controlled airflow environment and its design offers an affordable and practical solution for researchers and students to conduct their aerodynamic experiments on small-scale models. The paper outlines key considerations for designing and constructing the wind tunnel, including selected blower fan and design of the fan holder structure. The wind tunnel is successfully constructed and tested, and the results have shown that the airflow with an average of 4 m/s and turbulence intensity of 15%. Through its capacity to provide a wide range of turbulence intensities (i.e. 15% - 89%), this wind tunnel empowers researchers to explore an extensive spectrum of real-world conditions, ensuring that the experimental data more authentically mirrors the dynamic characteristics of outdoor environments. This enhanced versatility in turbulence intensity is of particular importance, especially given the marked variations in turbulence levels that have been evident across the different urban locales. Consequently, this study not only furnishes the practical guidance for constructing small open jet wind tunnels but also highlights the critical significance of regulating turbulence intensity, varying between 89% at a distance of 200 mm and 15% at 2000 mm from the outlet to ensure precise experimental fidelity.